Perancangan Website E-commerce Pada Toko Online Alvia Store - Triananda Fauzan Adicandra; Muhammad Rusli (UNIVERSITAS KALBIS, 2023)
Alvia Store is an online shop that sells women's clothing and accessories, the business flow process at the Alvia store is still very conventional, namely the sales system is still fairly manual which makes the process inefficient. Therefore, the author is here to provide a solution for the Alvia store, so that the sales system becomes easier and more practical. The author tries to change the Alvia store to be integrated and computerized in the flow of its business processes. With the aim of making a sales system based on an e-commerce website at the Alvia store, using the waterfall development method on an online sales system using the Prestashop CMS. The results of the research that the author did were in the form of a website-based e-commerce system, which made it easier for customers or sellers in the sales system.